Penggunaan Teknologi Informasi dan Komunikasi dalam Sistem Manajemen Pembelajaran pada Masa Pandemi Covid 19 - Adisel Adisel; Ahmad Gawdy Prananosa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study is to examine the use of information technology in management systems in tertiary institutions in Indonesia which are still not maximally and evenly utilized both in terms of equipment and management. This research is an international journal study. The results of input resource research include visualizer / document camera, computer, whiteboard, student response system, and application program. Output resources include projectors, interactive whiteboards, and displays: monitors, televisions and more. Finally, other ICT equipment includes digital cameras, switchers, digital recorders, and other innovations. Conclusions, discussion of solutions to overcome obstacles in the form of uneven infrastructure that supports the application of this technology in education and the unpreparedness of human resources to utilize information and communication technology in the learning process. Keywords: Information Technology, Communication, Learning Management